The Relationship between Teacher Time Management Skills and Learning Effectiveness at SD Ma'arif Tieng - Indra Afandi; Jumintono Jumintono; Saryanto Saryanto (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the implementation of the Monokasope (Monopoli Kartu Soal Persegi) method and its effectiveness in improving mathematics learning outcomes and student engagement in learning perimeter and area of squares among third-grade students at SD Ma’arif Tieng. The study employed a qualitative literature-based analysis supported by recent findings on game-based learning and mathematics education. The results indicate that the Monokasope method creates an interactive, enjoyable, and student-centered learning environment by integrating educational game elements into classroom instruction. The method encourages active participation, collaborative problem-solving, and immediate feedback, which contribute to deeper conceptual understanding and improved mathematical achievement. Furthermore, Monokasope enhances students’ behavioral, emotional, cognitive, and social engagement by increasing motivation, attention, participation, and interaction during learning activities. The findings suggest that the implementation of Monokasope effectively supports the achievement of learning objectives while fostering positive attitudes toward mathematics. Therefore, Monokasope can be considered an innovative instructional strategy that improves both mathematics learning outcomes and student engagement in elementary school classrooms.